Combustion behaviour and slagging tendencies of pure, blended and kaolin additivated biomass pellets from fen paludicultures in two small-scale boilers < 30 kW. (September 2022) - Kuptz, Daniel; Kuchler, Carina; Rist, Elisabeth; Eickenscheidt, Tim; Mack, Robert; Schön, Claudia; Drösler, Matthias; Hartmann, Hans
Abstract: Pure, blended and additivated biomass pellets from four fen paludicultures were produced at TFZ and combusted in two small-scale biomass boilers (15 kW, 30 kW). Feedstocks derived from straw of Typha ssp., Phragmites australis, Phalaris arundinacea and Carex ssp. that were harvested during winter 2018, 2019 (used for pelletization) and 2020. Additivation of fuels with kaolin before pelletization or blending of fuels with EN plus wood pellets (A1 quality) after pelletization were applied. Straw and pellets were analyzed for physical and chemical fuel properties according to international standards for solid biofuels. Physical properties of pellets met the requirements of ISO 17225–6. Chemical properties of Typha indicated high TPM emissions due to high contents of K and Na in fuels while severe slagging was predicted for the other species by a high molar (Si + K + Al)/(Ca + Mg + P) ratio. During combustion in both boilers, CO and total particulate matter (TPM) emissions were high for Typha but slightly reduced by additivation with 2.3% kaolin. Blending of fuels significantly reduced NOX, SOX and HCl emissions due to lower N, S and Cl concentrations. Slagging was high for pure and additivated pellets of Phragmites, Phalaris and Carex with >50% of total ash consisting of particles >2 mm. No steady-state boiler operation could be achieved with either pure or additivated fuels. In conclusion, paludiculture pellets are challenging fuels for small-scale combustion plants. Their use cannot be recommended for the tested boilers. Technical solutions may be easier applied in medium sized combustions plants above 100 kW. Highlights: Fuel quality and combustion behaviour of paludiculture straw & pellets were analyzed. Additivation (kaolin) and blending (wood) were applied to improve combustion. CO & TPM emissions were high for Typha while slagging was high for all other fuels. NOX emissions were significantly increased for paludicultures but improved by blending. Kaolin had only minor effects on combustion due to overall low additivation levels.